Sex and gender aspects in clinical medicine - Oertelt-Prigione, Sabine,Regitz-Zagrosek, Vera (Springer, 2011)
This concise and practical book focuses not on women's health, but on the presentation of differences in clinical symptoms, management and outcomes in women and men. All chapters include tables on sex/gender differences in symptoms and management. Intro – Sex and Gender Aspectsin Clinical Medicine – Contents – Contributors – Abbreviations – 1: Why Do We Need Gender Medicine? – 1.1 The Evolution of Gender Medicine – 1.2 How to Defi ne Gender Medicine? – 1.3 Gender Leads to Improvementsin Medical Care – 1.3.1 Better Understandingof Pathophysiology, Risk Factors,and Clinical Manifestations – 1.3.2 Increasing Effi ciency in TherapeuticInterventions – 1.4 Research Fields in Gender Medicine – 1.4.1 Basic Research – 1.4.2 Clinical Studies – 1.4.3 Pharmacology – 1.4.4 Epidemiology, Health Care,and Prevention Research – 1.5 Gender and Personalized Medicine – 2: Gendered Innovations in Biomedicine and Public Health Research – 2.1 Fixing the Numbers of Women in Science and Medicine – 2.2 Fixing the Institutions: Transforming Structures and Removing Barriers – 2.3 Fixing the Knowledge: Enhancing Excellence by Mainstreaming Gender Analysis into Basic and Applied Research – 2.4 Moving Forward – References – 3: Sex and Gender in Medical Literature – 3.1 Sex and Gender in Medicine – 3.2 Gender in Authorship of Medical Publications – 3.3 Gender-Specific Analysis in Research Publications – 3.4 Inclusion of Sex and Gender into Medical Guidelines and Product Labeling – References – 4: Sex and Gender Differences in Cardiovascular Disease – 4.1 Introduction – 4.2 Myocardial Infarction – 4.2.1 Epidemiology – 4.2.2 Pathophysiology – 4.2.3 Clinical Manifestation – 4.2.4 Management – 4.2.5 Outcomes – Take Home Messages – 4.3 Coronary Artery Disease (CAD) – 4.3.1 Epidemiology – 4.3.2 Pathophysiology – 4.3.3 Clinical Manifestation – 4.3.4 Management – 4.3.5 Outcomes – Take Home Messages – 4.4 Hypertension – 4.4.1 Epidemiology – 4.4.2 Pathophysiology – 4.4.3 Clinical Manifestation – 4.4.4 Management – 4.4.5 Outcomes – Take Home Messages.
Description based on publisher supplied metadata and other sources
Keywords: Clinical medicine; Clinical Medicine; Men's Health; Sex Factors; Women's Health; Internal medicine; Electronic books